(untitled) (Journal of history-rus, 2022)
The signs that arise on the basis of any informational comprehension and perception in a person’s life are formed due to his character and worldview. It should be noted that such symbols, which communicate the beliefs of the people, are formed depending on the environment and customs of the people themselves. Such symbols include color and numeric characters. Traditions, customs, culture and beliefs of any people in the world, preserved for centuries, reflect their characteristics through the acceptance and understanding of natural forces.It is easy to see that each of them has its own characteristics of perception, depending on the differences in their own history and culture. For example, it should be noted that the perception of a certain color is different for various peoples, and sometimes they give opposite definitions. That is, according to the understanding that has long been established among every people, we can see both the similarity and the opposite of perception in color and numerical judgments. In any case, we should consider all this as information, information and auxiliary tools that will help in the study of the history, culture and worldview of the people. That is why it is important to take into account color and number, which are considered one of the philosophical and logical categories that show space and time, nature, as well as the relationship between society and human, which are also used as a symbolic indicator in the worldview of people, the perception of natural phenomena, their habitat, geographic location.